Epistemic and Chronological Criticism in the Safīnah Kallā Saya‘lamūn Exegesis Surah Ar-Rūm [30]:1–5 - Masgun Arifin; Ahmad Nabilul Maram (Pusat Penelitian dan Pengabdian pada Masyarakat (P3M) Sekolah Tinggi Agama Islam As-Sunnah, 2026)
This discourse examines the Safīnah Kallā Saya‘lamūn exegesis, which employs historical analogies to demonstrate the relevance of the historical content in the Qur’an; however, the criteria for testing these claims against empirical history remain underdeveloped. This study proposes a “Chronological-Epistemic Evaluation” model to critique the use of historical analogies in Indonesian exegetical works, particularly the Tafsir Safīnah Kallā Saya‘lamūn, which interprets Surah Ar-Rūm [30]:1–5 by claiming a date correspondence (17 Ramadan/August 17) and stating that a discrepancy of one or two days is permissible across all calendars. Through qualitative research, this study employs an astronomical algorithm for Hijri-Gregorian conversion to verify the claim of a direct temporal correspondence between the Roman victory (7th century) and Indonesian Independence (1945). The research findings indicate that the text operates through a